1990
DOI: 10.1111/j.1756-1051.1990.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the secretory glands of Hiptage sericea (Malpighiaceae)

Abstract: Inamdar, J . A . 1990. Studies in the secretory glands of Hiptage sericea (Malpighiaceae). -Nord. J. Bot. 10: 5 7 4 2 . Copenhagen. ISSN 0107-055X.Hipfage sericea is shown to possess both lipophilic glands and extrafloral nectaries. Both types of glands develop from a group of initials and show similarities in organisation of tissue systems and secretion. The nature of the secretory substances is however different. The occurrence and function of the glands are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…According to Vogel (1990), the transformation of nectaries into elaiophores must have happened in response to the mutualism between flowers of species of Malpighiaceae and wild bees of tribe Centridini. Subramanian et al (1990) studying Hiptage sericea and Castro et al (2001) analyzing G. brasiliensis both reached the same conclusion and considered that these structures are homologous. In the same way, Durkee et al (1984) suggested that the EFNs of Passiflora foetida represent a transition to lipid-secreting glands.…”
Section: Discussionsupporting
confidence: 49%
“…According to Vogel (1990), the transformation of nectaries into elaiophores must have happened in response to the mutualism between flowers of species of Malpighiaceae and wild bees of tribe Centridini. Subramanian et al (1990) studying Hiptage sericea and Castro et al (2001) analyzing G. brasiliensis both reached the same conclusion and considered that these structures are homologous. In the same way, Durkee et al (1984) suggested that the EFNs of Passiflora foetida represent a transition to lipid-secreting glands.…”
Section: Discussionsupporting
confidence: 49%
“…In these species, the glands are smaller, intersepalics and seems to be related with extrafloral nectar secretion, the pollen being the only reward to the pollinators (Vogel 1974;1990a). Nevertheless, there is a report suggesting lipophilic secretions by the sepal glands of a paleotropical species, Hiptage sericea (Subramanian et al 1990).…”
Section: Malpighiaceaementioning
confidence: 99%
“…Externally, the sepal glands are morphologically very similar among most species, being oval and sessile or short-stalked (see Vogel 1974;Subramanian et al 1990;Mamede 1993;Laskowski & Bautista 1999;Castro et al 2001;Possobom 2013;Possobom et al 2015;Araújo & Meira 2016). Long-stalked elaiophores occur only in Dinemagonum, Dinemandra, Heladena and Henleophytum species (Simpson 1989;Cocucci et al 1996).…”
Section: Malpighiaceaementioning
confidence: 99%
“…The New World Malpighiaceae principally have bilaterally symmetrical flowers that are mainly pollinated by oil-collecting bees, whereas most African taxa are radially symmetrical. Such radially symmetrical flowers in African genera are thought to be an adaptation as a result of the rotating Subramanian et al (1990); this study movements used by certain insects on flowers, which makes the flag petal unnecessary for orientation by these visitors (Davis, 2002). In the Asian H. benghalensis, however, mirror-image flowers require pollinators entering via the space between the style and the pollinating stamen to transfer pollen successfully between left-and right-styled flowers.…”
Section: Discussionmentioning
confidence: 95%